Pendekatan Deep learning Pada Pembelajaran di Sekolah Dasar - Raja, Faisal Hamid Maka; Ayub, Daeng; Ramadani, Rika Fitri; Fahmi, Rahmat; Pramono, Basuki (Program Studi Pendidikan Masyarakat, 2026)
Abstract: Learning in elementary school is an important foundation for developmentcognitiveand affective. Currently, the approachdeep learningIt is increasingly gaining attention because it emphasizes conceptual understanding, reflection, and problem solving. The aim of this research is to obtain an objective picture of elementary school teachers' understanding, application, and perceptions of this learning approach.deep learningThis study used a descriptive survey method, conducted by distributing questionnaires to 50 elementary school teachers in Wolowaru sub-district. This study was conducted in 10 elementary schools in Wolowaru sub-district for approximately one month. In addition, a literature review was conducted from national and international journals discussing the implementation ofdeep learningin basic learning. The research results show thatdeep learningIn the context of education, it refers not only to artificial intelligence technology, but also to an in-depth learning approach that encourages holistic, reflective, and meaningful conceptual understanding. Despite its potential to improve students' conceptual understanding and critical thinking, its implementationdeep learningstill facing challenges in terms of curriculum, teacher training, and supporting facilities. Abstrak: Pembelajaran di SD menjadi dasar penting bagi perkembangan kognitif dan afektif. Saat ini, pendekatan deep learning semakin dilirik karena menekankan pemahaman konsep, refleksi, dan pemecahan masalah. Tujuan penelitian untuk memperoleh gambaran yang objektif tentang pemahaman, penerapan, dan persepsi guru SD terhadap pendekatan pembelajaran deep learning. Penelitian ini menggunakan metode survei deskriptif dilakukan dengan menyebarkan kuesioner kepada 50 guru SD di wilayah kecamatan wolowaru. Penelitian ini dilaksanakan di 10 (Sepuluh) Sekolah Dasar kecamatan wolowaru selama kurang lebih satu Bulan. Selain itu, dilakukan kajian literatur dari jurnal nasional dan internasional yang membahas penerapan deep learning dalam pembelajaran dasar. Hasil penelitian menunjukan bahwa deep learning dalam konteks pendidikan bukan hanya merujuk pada teknologi kecerdasan buatan, tetapi juga pada pendekatan pembelajaran mendalam yang mendorong pemahaman konsep secara holistik, reflektif, dan bermakna. Meskipun potensial meningkatkan pemahaman konsep dan berpikir kritis siswa, implementasi deep learning masih menghadapi tantangan dalam hal kurikulum, pelatihan guru, dan sarana pendukung.